Progression of Nonmotor Symptoms in Parkinson’s Disease by Sex and Motor Laterality - Zimple Kurlawala; Paul H. Shadowen; Joseph D. McMillan; Levi J Beverly; Robert P. Friedland (Parkinson's Disease)
Nonmotor symptoms (NMS) in Parkinson’s disease (PD) can start up to a decade before motor manifestations and strongly correlate with the quality of life. Understanding patterns of NMS can provide clues to the incipient site of PD pathology. Our goal was to systematically characterize the progression of NMS in PD (n = 489), compared to healthy controls, HC (n = 241), based on the sex of the subjects and laterality of motor symptom onset. Additionally, NMS experienced at the onset of PD were also compared to subjects with scans without dopaminergic deficit, SWEDD (n = 81). The Parkinson’s Progression Markers Initiative (PPMI) database was utilized to analyze several NMS scales. NMS experienced by PD and SWEDD cohorts were significantly higher than HC and both sex and laterality influenced several NMS scales at the onset of motor symptoms. Sex Differences. PD males experienced significant worsening of sexual, urinary, sleep, and cognitive functions compared to PD females. PD females reported significantly increased thermoregulatory dysfunction and anxious mood over 7 years and significantly more constipation during the first 4 years after PD onset. Laterality Differences. At onset, PD subjects with right-sided motor predominance reported significantly higher autonomic dysfunction. Subjects with left-sided motor predominance experienced significantly more anxious mood at onset which continued as Parkinson’s progressed. In conclusion, males experienced increased NMS burden in Parkinson’s disease. Laterality of motor symptoms did not significantly influence NMS progression, except anxious mood. We analyzed NMS in a large cohort of PD patients, and these data are valuable to improve PD patients’ quality of life by therapeutically alleviating nonmotor symptoms.